Transdutor de modo ortogonal compacto com portas de interface simétricas - Gerhardt, Lissandro (2019)
A broadband radio link connection must strictly follow the specifications of the telecommunications regulatory of each country. With the rational use of the spectrum it is possible to establish radio links with less interference, allowing companies competing in this market segment without interfering each other. Over the years, it has become hard to find free spectrum bands. One way to enhance the rational use of the spectrum is through links that operate in dual polarization. To validate this statement, it is necessary that the link operates both polarizations exactly at the same channel. As a result, radio and antenna industry needs to find new ways so that the equipment allows simultaneously the use of two channels isolated only by polarization of the electromagnetic wave in their devices. An essential device that promotes this feature is the Orthomode Transducer. This device is responsible for separating two electromagnetic waves that travels in a waveguide in orthogonal distinct polarizations with respect to each other, making them available in two interface ports, each signal in an isolated way. The Orthomode Transducer is located between the antenna and the radio equipment. In this dissertation, the research and development of an Orthomode Transducer was carried out using a new symmetrical coupling concept, in the form of a "T". Such innovative geometry has resulted in a compact device, with low loss, high isolation between ports, and up to 20% of bandwidth. The research results of this new geometry device were carried out with the support of an electromagnetic simulation software. Practical results are also presented through the construction of a functional prototype, as well as laboratory measurements.